Single-dose of a replication-competent adenovirus-vectored vaccine provides sterilizing protection against Rift Valley fever virus challenge - Bian, Ting; Wang, Busen; Fu, Guangcheng; Hao, Meng; Chen, Yi; Fang, Ting; Liu, Shuling; Yu, Changming; Li, Jianmin; Chen, Wei (Frontiers in Immunology, 2022)
Rift Valley fever virus (RVFV) is one of the most important virulent pathogens causing severe disease in animals and humans. However, there is currently no approved vaccine to prevent RVFV infection in humans. The use of human adenovirus serotype 4 (Ad4) as a vector for an RVFV vaccine has not been reported. Here, we report the generation of a replication-competent recombinant Ad4 vector expressing codon-optimized forms of the RVFV glycoproteins Gn and Gc (named Ad4-GnGc). Intramuscular immunization with Ad4-GnGc elicited robust neutralizing antibodies against RVFV and cellular immune responses in mice. A single low-dose vaccination with Ad4-GnGc completely protected interferon-α/β receptor-deficient A129 mice from lethal RVFV infection. More importantly, Ad4-GnGc efficacy was not affected by pre-existing immunity to adenovirus serotype 5, which currently exists widely in populations. These results suggest that Ad4-GnGc is a promising vaccine candidate against RVFV.